Leaf and grain morphology of Glycine max L. using digital images - Sauceda-Acosta, Carlos Patricio; Rodríguez-Cota, Franklin Gerardo; Borbón-Gracia, Alberto; Beltrán-Peña, Hugo; Sánchez-Portillo1, Juan Fernando; Sauceda-Acosta, Raúl Hipólito (Revista Mexicana de Ciencias Agrícolas, 2024)
Leaf and grain morphology of soybean (Glycine max L.) is necessary to identify varieties and explain their agronomic behavior, but it requires quantitative and easy-to-obtain measurements. This can be solved by digital image analysis (DIA); therefore, it was implemented to evaluate the leaf and grain morphology in the Cajeme, Guayparime S-10, and Harbar ’88 varieties. The DIA was automated in ImageJ 1.51 t to measure size, length, width, circularity, and color in leaflets (cm) and grains (mm). Specific leaf area (SLA, cm2 g-1), total grain area (TA, mm2), number of pods (NPP) and grains per plant (NGP), hectoliter weight (HEW, kg hl-1) and 100 grains (WHG, g) were also measured. The central leaflet was elliptical in shape, larger in size, and had SLA (p≤ 0.05), while the lateral ones were oval. Leaflet area (LA) was correlated (p≤ 0.01) with length, width, and their product (r≥ 0.93). Cajeme showed different leaf color (p≤ 0.01); Guayparime S-10 had higher LA, HEW, NPP and NGP but a grain that is smaller in size, length and width (p≤ 0.01). WHG was associated (p≤ 0.01) with TA (rs= 0.89), size (rs= 0.88), grain length and width (rs≥ 0.71), and leaf size (rs= -0.5). Harbar ’88 showed brighter grain, and Guayparime S-10 smaller grain (p≤ 0.01). The circularity of the leaflet facilitates the objective classification of the shape. The DIA is useful for phenotyping; it allows the identification of differences in leaflets and grains of the Cajeme, Guayparime S-10, and Harbar ’88 varieties.
Keywords: Glycine max; color; ImageJ; shape; size